B-Codes and their relationship with alternative codes - Ngo, Hien Thi (Journal of Computer Science and Cybernetics, 2018)
Codes of bounded words (b-codes, <>-codes), an extension of the notion of ordinary codes, have been first introduced and considered by P. T. Huy et al. in 2009. In this note, we consider some new subclasses of b-codes. In particular, characteristic properties of such codes are established. Also, relationship between b-codes, alternative codes and their subclasses are considered.